Missionary Position: The Irony of Translational Activism in Colonial Orissa - K. Dash, Debendra; R. Pattanaik, Dipti (TTR)

(untitled) (Association canadienne de traductologie, 2005)
Translating was crucial to the missionary project everywhere, especially after the Protestant Reformation. In their competition to expand their reach, various denominations of missionaries not only translated the Scriptures into the various local languages where they went, but also mediated various modern institutions like the school system, health-care and print-technology in those traditional societies. These institutions and the activity of translation were often the means to achieve the ultimate goal of proselytization. Their rate of success in achieving their goal in different places varied for several reasons. In places like Orissa where there was a deep-rooted cultural and religious tradition, their rate of success was very low. Even the forces of modernity they tried to mediate were regarded with suspicion for a long time on account of the peculiar political condition prevalent in Orissa at that time. Their activism in Orissa during the early part of 19th century was conflated with colonial hegemony. Moreover, the racial and cultural pride of missionaries prevented them from respecting the local condition and culture. Therefore, the translations they undertook were perceived as ridiculous and were summarily rejected. Orissa already had a long literary-cultural and translatory practice. The missionary challenge, however, helped in reorienting and galvanizing this tradition in a specific way. Although the missionaries largely failed in achieving their primary goal, their activism ironically helped in the growth of a new synthetic translational and literary culture in Orissa, long after their influence had waned.Keywords: sub colonialism, cultural coding, translational activism, bhāsā language, oral culture.